GPRC6A regulates prostate cancer progression - Pi, Min (2011)
BACKGROUND: GPRC6A is a nutrient sensing GPCR that is activated in vitro by a variety of ligands, including amino acids, calcium, zinc, osteocalcin (OC) and testosterone. The association between nutritional factors and risk of prostate cancer, the finding of increased expression of OC in prostate cancer cells and the association between GPRC6A and risk of prostate cancer in Japanese men implicates a role of GPRC6A in prostate cancer. METHODS: We examined if GPRC6A is expressed in human prostate cancer cell lines and used siRNA-mediated knockdown GPRC6A expression in prostate cancer cells to explore the function of GPRC6A in vitro. To assess the role GPRC6A in prostate cancer progression in vivo we intercrossed Gprc6a(−/−) mice onto the TRAMP mouse prostate cancer model. RESULTS: GPRC6A transcripts were markedly increased in prostate cancer cell lines 22Rv1, PC-3 and LNCaP, compared to the normal prostate RWPE-1 cell line. In addition, a panel of GPRC6A ligands, including calcium, OC, and arginine, exhibited in prostate cancer cell lines a dose-dependent stimulation of ERK activity, cell proliferation, chemotaxis, and prostate specific antigen and Runx 2 gene expression. These responses were inhibited by siRNA-mediated knockdown of GPRC6A. Finally, transfer of Gprc6a deficiency onto a TRAMP mouse model of prostate cancer significantly retarded prostate cancer progression and improved survival of compound Gprc6a(−/−)/TRAMP mice. CONCLUSIONS: GPRC6A is a novel molecular target for regulating prostate growth and cancer progression. Increments in GPRC6A may augment the ability of prostate cancer cells to proliferate in response to dietary and bone derived ligands.